IMPLEMENTASI REST API DALAM PENGEMBANGAN BACKEND INVENTORY PEMINJAMAN - Farchani, Saofikh Bagus; Hermanto, Nandang; Kusuma, Bagus Adhi (STKIP PGRI Tulungagung, 2025)
Inventory management is a crucial element for organizations that have assets to be monitored and managed effectively. In the era of information technology, web-based inventory systems have become a leading solution, enabling real-time inventory management and enhancing operational efficiency. This study focuses on the implementation of a REST API using Node.js in the development of an inventory system for Balai Desa Widarapayung Kulon. Node.js, with its ability to handle asynchronous requests, offers high efficiency in managing workloads. This study includes the design, development, and implementation of a REST API that connects the frontend application with the backend database, as well as identifying challenges and opportunities in using Node.js in a local environment. Through the Waterfall method, which includes requirement analysis, system design, implementation, integration and testing, deployment, and maintenance, this system is expected to provide optimal and adaptive services. Sustainable maintenance ensures the system remains reliable, secure, and capable of meeting user needs. The results show that this automated inventory system improves operational efficiency, transparency, and accountability in public asset management at Balai Desa Widarapayung Kulon, and provides an example for other local entities in utilizing technology to enhance service quality and asset management.